2011
DOI: 10.3892/etm.2011.399
|View full text |Cite
|
Sign up to set email alerts
|

miR-196a2 polymorphisms and susceptibility to cancer: A meta-analysis involving 24,697 subjects

Abstract: Abstract. An increasing number of studies have shown that the hsa-miR-196a2 rs11614913 polymorphism occurs in different types of cancer, but the results are generally controversial and inadequate, mainly due to limited statistical power. To resolve this issue, the present meta-analysis was carried out. Databases, including PubMed and Embase, were searched using: (miR-196a2 . Crude odds ratios (ORs) with 95% confidence intervals (CIs) were summarized in forest plots and detailed in tables. A total of 20 studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“…of human genome [10]. Recently, various studies focused on the pre-miRNA polymorphisms located on the stem-loop, such as pre-mir-196a2 rs11614913 [20], pre-mir-146a rs2910164 [21], pre-mir-499 rs3746444 [22,23]. In the present study, the G allele of pre-let7d rs10993081 was found to contribute an independent increased risk for MetS and this association may be partially due to its effect on glucose metabolism.…”
Section: Fig 3 Interaction Dendrogramsupporting
confidence: 48%
“…of human genome [10]. Recently, various studies focused on the pre-miRNA polymorphisms located on the stem-loop, such as pre-mir-196a2 rs11614913 [20], pre-mir-146a rs2910164 [21], pre-mir-499 rs3746444 [22,23]. In the present study, the G allele of pre-let7d rs10993081 was found to contribute an independent increased risk for MetS and this association may be partially due to its effect on glucose metabolism.…”
Section: Fig 3 Interaction Dendrogramsupporting
confidence: 48%
“…Several molecular epidemiological studies have investigated the association between the miR-149 rs2292832 polymorphism and cancer (Ding et al, 2013;Dominguez 2013), and the association of miR-149 rs2292832 polymorphism with cancer risks (Hu et al, 2009;Tian et al, 2009;Tu et al, 2012;Wang et al, 2012;Hong et al, 2013) have been conducted. But the conclusions are inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Two of them investigated rs2910164 in miR-146a [19], [22] while four studies focused on rs11614913 in miR-196a2 [18], [21], [23], [25]. Meta-analyses from Tian et al [24] and Xu et al [20] covered both of the two SNPs.…”
Section: Discussionmentioning
confidence: 99%